Removing Oil Impurity by Using Biomass Cell of Water Hyacinth - Abdillah, Fauziah (Universiti Teknologi PETRONAS, 2016)
Water Hyacinth (Eichhornia crassipes) is one of the world’s worst invasive aquatic plant which often found covered the river and pound. Recently, some studies show the feasibility of water hyacinth as oil sorbent for oil spill clean-up. Compare to its leaf and root, the stem of water hyacinth has the highest oil sorption capacity and buoyancy, even though has the smallest surface area. Increasing its surface area may result in higher sorption capacity. Active surface area can be potentially increased by treating the stem either physically, chemically or both. This study is aimed to increased surface area of water hyacinth’s stem by treating it with 3% of Hydrochloric acid (HCl). The characteristics of HCl treated sorbent and non-treated were compared and their sorption capacity towards diesel, gasoline, toluene, and hexane were also analysed in this study.